Effect of Using Local Fishmeal (Liza abu) as Protein Concentration in Broiler Diets - Jassim, Jaffer M. (International Journal of Poultry Science, 2010)
A total of 150 day-old chicks were fed five diets consisted of 0, 25, 50, 75 and 100% local fish meal instead of imported protein concentration. The trail lasted for 42 days. All fish meal levels chicks obtained similar body weight, feed consumption, feed conversion and mortality to those of control group. The percentage of carcass protein was significantly (p<0.05) increased, while the percentage of fat significantly (p<0.05) decreased. Tenderness and juiciness were not affected by the fish meal levels. The fish flavor of chicks carcasses was observed in the diets contains 75 and 100% local fishmeal.